Ion exchange membranes : fundamentals and applications - Tanaka, Yoshinobu (Amsterdam, Netherlands : Elsevier Ltd., 2015)
Fundamental study and industrial application of ion exchange membranes started over half a century ago. Through ongoing research and development, ion exchange membrane technology is now applied to many fields and contributes to the improvement of our standard of living. Ion Exchange Membranes, 2nd edition states the ion exchange membrane technology from the standpoint of fundamentals and applications. It discusses not only various phenomena exhibited by membranes but also their applications in many fields with economical evaluations. This second edition is updated and revised, featuring ten expanded chapters. New to this edition is a computer simulation program of ion-exchange membrane electrodialysis for water desalination that provides a guideline for designing, manufacturing and operating a practical-scale electrodialyzer. Meant to replace experiments, this program will be an important asset to those with time and monetary budgets.
8.3 Mass Transport Effect of a Spacer8.4 Dead Space Around a Spacer and Limiting Current Density; 8.5 Flow Pattern Image in a Flow Channel; 8.6 Flow Pattern and Limiting Current Density; 8.7 Local Flow Distribution in a Flow Channel; 8.8 Solution Velocity Distribution Between Desalting Cells; 8.9 Air Bubble Cleaning of a Flow Channel; 8.10 Solution Flow and Mass Transport in a Channel without a Spacer; 8.11 Velocity Profile in a Flow Channel with a Spacer; 8.12 Spacer Mesh Step Model and Mass Transport in a Boundary Layer; 8.13 Spacer Geometry and Pressure Drop in a Flow Channel.
Includes bibliographical references and index.
Vendor-supplied metadata.
Elsevier
Keywords: Ion-permeable membranes; SCIENCE / Chemistry / Physical & Theoretical; Ion-permeable membranes; Electrodialysis; Ion-permeable membranes; Membranes (Technology); Electronic books